Optional treatment of renal anemia - Wanic-Kossowska, Maria; Kozioł, Lidia; Szczepańska, Agnieszka (Przewodnik Lekarza/Guide for GPs, 2009)
Anemia, due to lack of erythropoietin, is a serious complication in nondialysed patients with chronic kidney disease (CKD). Anemia treatment with erythropoietin stimulating agents permit achieve target hemoglobin level in nondialysed patients with CKD. Anemia treatment has a beneficial effect on the function and heart structure and prevents progressive development of cardiovascular complications in CKD patients.